2011
DOI: 10.3758/s13414-010-0082-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial attention and conscious perception: the role of endogenous and exogenous orienting

Abstract: Attention has often been considered to be a gateway to consciousness (Posner, Proceedings of the National Academy of Sciences of the United States of America, 91(16), 7398-7403, 1994). However, its relationship with conscious perception (CP) remains highly controversial. While theoretical models and experimental data support the role of attention in CP (Chica, Lasaponara, Lupiáñez, Doricchi, & Bartolomeo, NeuroImage, 51, 1205-1212, 2010; Dehaene, Changeux, Naccache, Sackur, & Sergent, Trends in Cognitive Scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
85
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(107 citation statements)
references
References 54 publications
(80 reference statements)
18
85
3
Order By: Relevance
“…For example, Kusnir et al (2011) found that an auditory cue eliciting phasic alerting improved participants’ ability to discriminate a near-threshold stimulus, especially when targets were temporally unpredictable. Concerning spatial attention, exogenous attention modulates conscious access (Chica et al, 2010, 2011), producing larger (and more consistent) effects than endogenous attention does (Chica et al, 2012). In order to broadly complete the theoretical framework on the relation between attention and conscious perception, modulations of the anterior network of executive control (the third attention network in Posner and Petersen’s model) over consciousness must also be explored.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For example, Kusnir et al (2011) found that an auditory cue eliciting phasic alerting improved participants’ ability to discriminate a near-threshold stimulus, especially when targets were temporally unpredictable. Concerning spatial attention, exogenous attention modulates conscious access (Chica et al, 2010, 2011), producing larger (and more consistent) effects than endogenous attention does (Chica et al, 2012). In order to broadly complete the theoretical framework on the relation between attention and conscious perception, modulations of the anterior network of executive control (the third attention network in Posner and Petersen’s model) over consciousness must also be explored.…”
Section: Introductionmentioning
confidence: 96%
“…Following Posner and Petersen’s model (Posner and Petersen, 1990; Petersen and Posner, 2012), attention can be dissected into alerting, orienting, and executive control networks. Previous literature has already explored alerting and orienting contributions to conscious perception (Wyart and Tallon-Baudry, 2008; Chica et al, 2010, 2011, 2012, 2016; Kusnir et al, 2011; Wyart et al, 2011; Chica and Bartolomeo, 2012; Botta et al, 2014). For example, Kusnir et al (2011) found that an auditory cue eliciting phasic alerting improved participants’ ability to discriminate a near-threshold stimulus, especially when targets were temporally unpredictable.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, recent work by Chica and Bartolomeo (e.g. Chica, Lasaponara, Chanes, Valero-Cabré, Doricchi, Lupiáñez et al, 2011;Chica, Botta, Lupiáñez & Bartolomeo, 2012;Chica, Paz-Alonso, Valero-Cabre & Bartolomeo, 2012) suggests that the coupling of attention and consciousness is much stronger when attention is under exogenous, as opposed to endogenous, control. That is, only when attention is captured automatically by external events (exogenously controlled), rather than voluntarily directed by the observer (endogenously controlled), is it not sufficient for awareness.…”
Section: General Introductionmentioning
confidence: 99%
“…From these competitive neural interactions, believed to be relatively slow, attention progressively emerges. The direction of the attention will depend on the result of the competitive interactions (Desimone and Duncan, 1995;Chica et al, 2011;Corbetta and Shulman, 2002;Pinto et al, 2013). This process is called "biased competition"; the attention given to an object is influenced or biased, by its intrinsic features and top-down processes to give priority to the most relevant stimuli (Desimone and Duncan, 1995).…”
Section: Brain Processesmentioning
confidence: 99%